Teacher-Students’ Relationship and Students’ Academic Performance in Public Secondary Schools in Magu District, Tanzania - Paschal, Mahona, Joseph; Mkulu, Demetria, Gerold (My University, 2021)
This study explored the influence of teacher – students’ relationship on students’ academic performance in Tanzania using Magu District as a case study. The sample for this study was 130 respondents that were drawn from six public secondary schools both by using rondom sampling and purposive sampling; 6 school Heads, 57 teachers, 66 students and one District Educational Officer. A descriptive survey approach was used in this study. In order to get information, the researcher used questionnaire and interview as instruments. The results of this study indicated that teacher–students’ relationship is a crucial determinant and catalyst to academic performance in Tanzanian public secondary schools. The study identified among others that teacher - students relationships helps students to feel cared for by their teachers, helps students to have freedom of expression in the classroom and help teachers and students to be an integral part of the classroom as they participate actively. From the findings, it is concluded that despite the fact that teachers and students were aware of the elements of teacher- students relationships poor teacher – student relationships were still recorded in schools. Therefore, it is recommended that teachers should introduce close relationshis with students. Also, the study recommended that, performance of students can only be attained if teacher – students relationships will be maintained
Keywords: Academic performance; Public Secondary Schools; Relationships; Teacher - student relationships